Adoption of project management methodologies in Colombia project manager's perspective (2018)
Project management is a discipline with broad global growth in recent years, judging by the growth in formal education programs, professional societies, editing of bodies of knowledge and certifications for practitioners in the discipline. This cross-sectional quantitative research identifies the degree of adoption of project management methodologies and analyzes the relationship of their application with the project success in the Colombian context. The results of this study suggest that there is no statistically significant relationship between the application of project management methodologies and the project success.